Understanding the experiences of mothers of children with stunting in two Egyptian communities focusing on the first 1000 days - Abdelgawad, Rana (AUC Knowledge Fountain, 2023)
Introduction: Egypt’s stunting prevalence is 13% with multiple initiatives and programs tackling child malnutrition. While many of them are promising, not all address the child’s first 1000 days, in addition to missing the cultural aspect for the Egyptian population which affects their dietary practices and health seeking behaviors. Goal: Determine what challenges mothers face for their child’s nutrition and what learnings from exemplars countries can help Egypt reduce the malnutrition and stunting problem Aim: Finding insights about the factors influencing child nutrition during 1st 1000 days and what programs can be implemented based on successful past experiences in exemplar countries. Objectives: 1. Exploring the challenges mothers face in their experience with their child’s nutrition during the first 1000 days. 2. Outline the scope of maternal and child health services available at primary health care facilities. 3. Develop learnings from key programs and police focusing on the first 1000 days in a child’s life in exemplar countries Methodology: A qualitative study in Al-Menoufia and Al-Gharbia governates in Egypt using in-depth interviews with 19 mothers of stunted children and 11 health care professionals. Interview data transcripts were manually coded, and themes were deductively and inductively developed. A narrative review of exemplar countries summarizing key initiatives and learnings from countries was done. Review was conducted in April 2023 including studies published in the last three years evaluating programs related to the stunting decline in exemplar countries Findings and Discussion: Mothers experienced poor health and nutrition affecting their child’s health and compromising the child’s breastfeeding. Poor incomes, lack of awareness on stunting consequences, improper complementary child feeding practices and grandmother’s influence on diet were main themes. Healthcare professionals shared poor resources, lack of trainings and inconsistent growth measurements as challenges they face while providing health services to patients. The narrative review for exemplar countries showed all exemplars recognizing the multifactorial nature of stunting and emphasized multisectoral collaboration. Exemplars succeeded to reduce stunting through nutrition sensitive and nutrition specific programs. Learnings for Egypt included programs addressing agriculture land reforms, innovation and technology, health and education system reforms with a focus on targeting high risk population and providing high quality services to ensure equity. Conclusion: Stunting in Egypt needs to be addressed through multiple initiatives tailored to the cultural context of Egypt in collaboration between multiple stakeholders.